1998
DOI: 10.1002/1529-0131(199801)41:1<150::aid-art18>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A novel NOD-derived murine model of primary Sj�gren's syndrome

Abstract: Objective. The appearance of autoimmune diabetes prior to autoimmune exocrinopathy in the NOD mouse suggests that it is an excellent model of secondary , but not primary, autoimmune sicca complications. Since the unique major histocompatibility complex (MHC) I-Ag7 expression in NOD mice is essential for the development of insulitis and diabetes in these animals, we investigated exocrine gland function in NOD.BlOJf2' mice, which have an MHC congenic to NOD, as a potential model for primary Sjogren's syndrome (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 130 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In the male NOD mouse, within the first 6 weeks of age lacrimal glands undergo markedly altered gene expression [19,20], including elevated expression of cathepsin, increased extra-cellular matrix degradation and altered lipid homeostasis [46,47]. These changes precede the massive accumulation of leukocytes that culminates in overt exocrinopathy by 12 to 16 weeks of age [48,49]. In this study, differential gene expression analysis with Affymetrix gene arrays showed that antagonism of the LTBR-axis altered the expression of a wide variety of genes related to lymphocyte trafficking, lymphocyte function and lacrimal gland function, and these changes coincided with improvement in tear fluid secretion and ocular integrity, two measures of overall ocular health.…”
Section: Discussionmentioning
confidence: 99%
“…In the male NOD mouse, within the first 6 weeks of age lacrimal glands undergo markedly altered gene expression [19,20], including elevated expression of cathepsin, increased extra-cellular matrix degradation and altered lipid homeostasis [46,47]. These changes precede the massive accumulation of leukocytes that culminates in overt exocrinopathy by 12 to 16 weeks of age [48,49]. In this study, differential gene expression analysis with Affymetrix gene arrays showed that antagonism of the LTBR-axis altered the expression of a wide variety of genes related to lymphocyte trafficking, lymphocyte function and lacrimal gland function, and these changes coincided with improvement in tear fluid secretion and ocular integrity, two measures of overall ocular health.…”
Section: Discussionmentioning
confidence: 99%
“…The T1D phenotype has a strong dependence on a single MHC haplotype, whereas the SS-like phenotype is far more permissive and a feature that has permitted separation of the two diseases. This was first demonstrated in the NOD.B10Sn- H2 b /J mouse derived by replacing the MHC locus of the NOD mouse first with the H-2b MHC of the C57BL/6 strain [29], then later with the H-2q MHC [30]. These recombinant inbred mice do not develop T1D, but continue to develop SS-like disease characterized by lymphocytic infiltration of the salivary and lacrimal glands, as well as pulmonary disease, renal disease, and autoantibodies [31, 32].…”
Section: Lessons Learned From the C57bl/6nod-aec1aec2 Mouse Modelmentioning
confidence: 99%
“…They have a strong female disease predilection and exhibit spontaneous disease development. Moreover, they display antinuclear autoantibodies, lymphocytic infiltrates in salivary and lacrimal tissues, and loss of salivary flow [19, 35]. Recent work demonstrates that MyD88 plays a crucial role in the development of pSS.…”
Section: Mouse Models Of Pss Reveal the Importance Of Tlrs In Diseasementioning
confidence: 99%